Statistics learning innovation through contextual numeration of literacy e-module - Nuranita Adiastuti; Rena Sageta; Zahra Khairun Nisa (Universitas Negeri Yogyakarta, 2025)
The numeracy literacy skills of Indonesian students, particularly in solving story problems and presenting statistical data, remain relatively low. However, teaching materials that effectively support numeracy literacy in mathematics are still limited. This study aims to describe the development of a numeracy literacy e-module as an alternative teaching material for statistics. Using a Research and Development approach within the ADDIE model, the study was conducted through the implementation stage due to time constraints. Participants included 30 seventh-grade students from Junior High School 2 Kuningan. Data were obtained from expert validation and student response questionnaires and analyzed descriptively using percentages. Validation results from material and media experts were 90.62%, 95.31%, and 94.12%, categorized as very valid. Student responses indicated a practicality level of 91.33%. The contextual story-based e-module effectively connects statistical concepts to real-life situations. The findings conclude that the developed e-module is highly valid and practical for classroom use. However, implementation faces challenges, including limited teacher training and inadequate digital infrastructure. Therefore, teacher training and better digital support are recommended, along with further studies to evaluate the long-term effectiveness of the e-module.